Challenges and innovations in CAR-T cell therapy: a comprehensive analysis - Luo, Jingming; Zhang, Xianwen (Frontiers in Oncology, 2024)
Recent years have seen a marked increased in research on chimeric antigen receptor T (CAR-T) cells, with specific relevance to the treatment of hematological malignancies. Here, the structural principles, iterative processes, and target selection of CAR-T cells for therapeutic applications are described in detail, as well as the challenges faced in the treatment of solid tumors and hematological malignancies. These challenges include insufficient infiltration of cells, off-target effects, cytokine release syndrome, and tumor lysis syndrome. In addition, directions in the iterative development of CAR-T cell therapy are discussed, including modifications of CAR-T cell structures, improvements in specificity using multi-targets and novel targets, the use of Boolean logic gates to minimize off-target effects and control toxicity, and the adoption of additional protection mechanisms to improve the durability of CAR-T cell treatment. This review provides ideas and strategies for the development of CAR-T cell therapy through an in-depth exploration of the underlying mechanisms of action of CAR-T cells and their potential for innovative modification.